PERANCANGAN DESAIN FORMULIR PERSETUJUAN TINDAKAN KEDOKTERAN ELEKTRONIK PASIEN RAWAT INAP DI UPTD PUSKESMAS TANJUNGANOM KABUPATEN NGANJUK - Deni Luvi Jayanto; Muhammad Mutafanninun; Nurhadi Nurhadi; Risa Helilintar (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
Doctors at the Tanjunganom Health Center UPTD use a medical action approval form before taking medical action. Baseded on the findings, the implementation of the medical action approval form at the Tanjunganom Health Center UPTD was difficult to read and the writing was not in accordance with the rules for documenting medical records. Whereas approval of medical action as evidence of legality in court and avoiding malpractice actions that harm patients. The purpose of the study was to design an electronic medical action approval form according to the needed of the officer, based on color, layout and control. This study used a qualitative descriptive, for the population and a sample of 2 inpatient registration officers who use informed consent. The result of this research is the interface design of the electronic medical action consent form. The results of interviews with 2 inpatient registration officers obtained that the colour uses light green as a colour symbol from the Tanjunganom Health Center, the layout was neatly arranged according to the comfort of the officers when using the application, and the controls used are icons and explanatory text adjusted to their functions so that the use of buttons was easy. understood. These results are adjusted to the needed of officers to make it easier for officers to operate the application. It should be realized immediately by organizing training, outreach to officers so that services are more effective and efficient.